Sleep trajectories and frequency of non-suicidal self-injury in adolescents: a person-oriented perspective over two years - S. V. Bauducco; L. Tilton-Weaver; M. Gradisar; M. Hysing; D. Latina (Scientific Reports)
Abstract Adolescent sleep quality and quantity is commonly linked to worse emotion regulation. One maladaptive emotion regulation strategy that is on the rise is non-suicidal self-injury (NSSI), which includes burning, hitting, or scratching one’s own body tissue without suicidal intent. The aim of this study was to explore the frequency of NSSI among different longitudinal trajectories of insomnia symptoms and short sleep duration to identify at-risk adolescents. We used questionnaire data collected annually (3 time points over 2 years) from a sample of Swedish adolescents (N = 1,294; Mage = 13.2 [range: 12–15 years], SD = 0.4; 46.8% girls). Adolescents answered questions about their sleep duration, symptoms of insomnia, NSSI, depressive symptoms, and demographics. Adolescents who reported persistent or increasing sleep problems over time also reported more NSSI. A notable pattern was that adolescents whose insomnia symptoms were high and increasing reported the highest frequency of NSSI, also compared to adolescents who started at the same high level of insomnia symptoms but improved over time. Therefore, measuring NSSI may help identify a risk-group for persistent sleep problems and self-injury. Because sleep disturbances, especially insomnia, and NSSI go hand-in-hand for most adolescents, sleep interventions would benefit the treatment and prevention of self-injury.